The Origins of Broadcast Education in the U.S. - James, Beverly (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Some ten years after the licensing of the first commercial radio station in the U.S.—Pittsburgh’s KDKA in 1920—radio courses began to appear in the curricula of what were then called speech departments, the forerunners of today’s communication departments. As outgrowths of existing courses in public speaking and drama, radio courses addressed such topics as announcing, diction, microphone techniques, directing, scriptwriting, singing, and acting. According to a survey conducted by the Federal Office of Education, some two dozen colleges or universities offered some version of a basic “radio speaking” course in 1933 (Koon 6-9). By the end ofthe decade, in many institutions the basic radio course had spun off separate classes in production, speech, writing, and other special topics, and several universities had begun to offer degrees in broadcasting (McReynolds 44-45).